Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

SIMPLIFY THIS!!!!!
7(y - 5) + 3y = 10(y +1)


Sagot :

The answer is the statement is false!
7(y-5)+3y=10(y+1)
Distribute the 7 to y and -5 and distribute 10 to y and 1
7y-35+3y=10y+10
Combine like terms
10y-35=10y+10
+35 to both sides
10y=10y+45
Subtract 10y from both sides and you’re left with 0=45 which is false- so the answer would be not true or there is no answer. Hope this helps!!!
Simplifying
7(y + -5) + 3y = 10y + 10

Reorder the terms:
7(-5 + y) + 3y = 10y + 10
(-5 * 7 + y * 7) + 3y = 10y + 10
(-35 + 7y) + 3y = 10y + 10

Combine like terms: 7y + 3y = 10y
-35 + 10y = 10y + 10

Reorder the terms:
-35 + 10y = 10 + 10y

Add '-10y' to each side of the equation.
-35 + 10y + -10y = 10 + 10y + -10y

Combine like terms: 10y + -10y = 0
-35 + 0 = 10 + 10y + -10y
-35 = 10 + 10y + -10y

Combine like terms: 10y + -10y = 0
-35 = 10 + 0
-35 = 10

Solving
-35 = 10

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.